2020
DOI: 10.1200/op.20.00489
|View full text |Cite
|
Sign up to set email alerts
|

Case of Fatal Immune-Related Skin Toxicity From Sequential Use of Osimertinib After Pembrolizumab: Lessons for Drug Sequencing in Never-Smoking Non–Small-Cell Lung Cancer

Abstract: DiagnosisCT, PET/CT and MRI brain: Stage IVB (T2b N3 M1) NSCLC EBUS: TTF1-positive adenocarcinoma ALK/ROS1 IHC negative, PD-L1 IHC negative, EGFR wild type (COBAS v2) ctDNA (Guardant 360) NGS reported: TP53 T125T mutation Tissue sample sent for orthogonal NGS (FoundationOne) Commenced carboplatin and pemetrexed chemotherapy Notified that there was insufficient tissue for orthogonal genotyping Repeat EBUS for molecular analysis Pembrolizumab added to cycles 3 and 4 of carboplatin and pemetrexed CT response eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…This association was also specific to osimertinib, with no severe IrAE seen with other EGFR TKIs 37 . Similarly, Cui and colleagues reported a case of fatal TEN from sequential use of osimertinib after pembrolizumab in an EGFR mutation positive lung cancer 38 . Our study had a patient who developed Grade 4 TEN from pembrolizumab use.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This association was also specific to osimertinib, with no severe IrAE seen with other EGFR TKIs 37 . Similarly, Cui and colleagues reported a case of fatal TEN from sequential use of osimertinib after pembrolizumab in an EGFR mutation positive lung cancer 38 . Our study had a patient who developed Grade 4 TEN from pembrolizumab use.…”
Section: Discussionsupporting
confidence: 68%
“…While the presence of EGFR mutation has never been reported as a risk factor for IrAE, serious IrAEs have been reported with concurrent use of tyrosine kinase inhibitor (TKI) and immunotherapy 36 . Recently, the sequential use of osimertinib following anti‐PD1 or anti‐PD‐L1 use has been reported to cause serious IrAEs in patients harbouring EGFR mutation 37,38 . A retrospective study conducted in Memorial Sloan Kettering Cancer Centre (MSKCC) showed that 15% of patients with EGFR mutation who had sequential treatment with anti‐PD‐1 or anti‐PD‐L1 inhibitors followed by osimertinib developed severe IrAEs, predominantly pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our data show a trend toward more TRAEs occurring when immunotherapy (alone, or combined with a chemotherapy) was the last treatment line received before selpercatinib; similar observations have been previously reported when the TKI osimertinib was administered following nivolumab or pembrolizumab. 25,26 However, because of the small sample size of the subgroups analyzed, these results must be interpreted with caution. Data from the LIBRETTO-001 study previously has been analyzed regarding an increased number of treatmentemergent hypersensitivity reactions in the subgroup of patients previously treated with immunotherapy prior to selpercatinib.…”
Section: Discussionmentioning
confidence: 99%
“… 1 2 This phenomenon has now been observed clinically, with hypersensitivity reactions to a number of pharmaceutical compounds shown to be exacerbated by the use of ICIs, 3 4 sometimes with fatal consequences. 5 …”
Section: Introductionmentioning
confidence: 99%
“…1 2 This phenomenon has now been observed clinically, with hypersensitivity reactions to a number of pharmaceutical compounds shown to be exacerbated by the use of ICIs, 3 4 sometimes with fatal consequences. 5 We report the case of a patient who developed Stevens-Johnson syndrome (SJS) to a previously tolerated iodinated contrast medium, amidotrizoate, after the use of atezolizumab, a PD-L1 blocker. We also present supporting in-vitro evidence that provides novel mechanistic insight.…”
Section: Introductionmentioning
confidence: 99%